Antimicrobial Effects of Garcinia Mangostana on Cariogenic Microorganisms - Janardhanan, Sunitha (J Clin Diagn Res, 2017)
INTRODUCTION: Garcinia mangostana commonly called as Mangosteen fruit has been used as an antibacterial agent since age old times. The mangosteen pericarp has proven to have antibacterial effect, but the effect of the same on cariogenic organisms has not been explored. The present study was an attempt to gain a better understanding of the antibacterial effect of mangosteen pericarp on the cariogenic bacteria, to unravel the therapeutic potential for the same. AIM: The aim of the study was to assess the antibacterial efficacy of the crude chloroform extract of mangosteen pericarp against cariogenic bacteria. MATERIALS AND METHODS: The study was done under laboratory settings using an in vitro design. The microorganisms namely Streptococcus mutans, Streptococcus sanguis, Streptococcus salivarius, Streptococcus oralis and Lactobacillus acidophilus were procured from American Type Cell Culture (ATCC) and Microbial Type Culture Collection (MTCC) were revived and lawn cultured. The antibacterial effect of mangosteen pericarp was tested using agar well diffusion method on Trypticase Soy Agar-Blood Agar (TSA-BA) and de Man, Rogosa and Sharpe (MRS) agar media. The standard antiplaque agent chlorhexidine was used as the positive control. This cross-sectional, experimental study was done in Central Research laboratory, Meenakshi Ammal Dental College for period of eight weeks. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values were determined by microbroth dilution method. Statistical analysis was done by calculating the mean of the zones of inhibition on tested microorganisms. Mann-Whitney test was done to compare the zones of inhibition of mangosteen and chlorhexidine. RESULTS: The antibacterial bioassay showed the highest activity for Lactobacillus acidophilus (13.6 mm) and Streptococcus sanguis (13.6 mm), whereas, it showed a medium and low activity for Streptococcus oralis (11.3 mm), Streptococcus mutans (10.6 mm) and Streptococcus salivarius (3 mm) respectively. The MBC and MIC values were lowest for Lactobacillus acidophilus (MIC 25 mg/ml, MBC 50 mg/ml) and Streptococcus oralis (MIC 50 mg/ml, MBC 100 mg/ml). CONCLUSION: Mangosteen pericarp extract had a higher zone of inhibition against the tested microorganisms which suggests its potent antibacterial action against cariogenic organisms. However, further analytical studies are needed to isolate the key molecules of mangosteen pericarp, to explore its anticariogenic therapeutic potential on gram negative oral microorganisms.